Volume 3: Design, Materials and Manufacturing, Parts A, B, and C 2012
DOI: 10.1115/imece2012-86265
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of Starch Based Bagasse Fiber Composite

Abstract: Environmentally-friendly, biodegradable, “green” composites were fabricated from starch-based matrix and bagasse (sugar cane waste) fibers. Native corn starch was mixed with glycerin and water, emulsified then added to the bagasse fibers previously prepared and treated by NaOH. The composite was preheated, then pressed for 30 minutes at 5 MPa and 170°C. SEM showed good adhesion between fibers and matrix up to 60wt% fibers. Density measurements showed low porosity for all composite samples up to 60wt% fibers. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…The moisture absorption dropped from 70 to 41% with increasing the BF content from 0 to 60%. Figure 8 shows a comparison between the moisture absorption of the TPS composites reinforced with 60 wt% fibers at the equilibrium plateau from the previously stated studies [13][14][15][16]. From Figure 8, it can be concluded that the moisture absorption is highly dependent on the fiber type, hence the cellulose content of the fibers.…”
Section: Composites From Renewable and Sustainable Materials 52mentioning
confidence: 69%
See 4 more Smart Citations
“…The moisture absorption dropped from 70 to 41% with increasing the BF content from 0 to 60%. Figure 8 shows a comparison between the moisture absorption of the TPS composites reinforced with 60 wt% fibers at the equilibrium plateau from the previously stated studies [13][14][15][16]. From Figure 8, it can be concluded that the moisture absorption is highly dependent on the fiber type, hence the cellulose content of the fibers.…”
Section: Composites From Renewable and Sustainable Materials 52mentioning
confidence: 69%
“…For flax, bagasse, banana, and date palm fiber (DPF) preparation took place by preheating the composite, pressing at 5 MPa and 150°C for 30 min [13][14][15][16]. Bamboo-reinforced starch composite was prepared by pressing at 20 MPa and 130 C for 5 min [17].…”
Section: Preparation and Characterizationmentioning
confidence: 99%
See 3 more Smart Citations